Endotoxic shock: Re-updating - Pacheco Romero, José (2015)
Yet we know the exact pathophysiology of endotoxic shock. Today we know that the main problem in this type of shock caused by endotoxins of gram-negative bacteria is not hypotension, but insufficient perfusion of the cell, which consequently brings mtabólicos disorders and alterations of the cell structure itself leading to irreversible shock and death.